2014
DOI: 10.1155/2014/107526
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of Radiosurgery in the Management of Radiation-Induced Meningiomas: A Review of Current Advances and Future Directions

Abstract: Meningiomas are among the most common primary adult brain tumors, which arise either spontaneously or secondary to environmental factors such as ionizing radiation. The latter are referred to as radiation-induced meningiomas (RIMs) which, while much less common than their spontaneous counterparts, are challenging from a management point of view. Similar to spontaneous meningiomas, the optimal management of RIMs is complete surgical resection. However, given their high grade, multiplicity, tendency to invade bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
(77 reference statements)
1
4
0
Order By: Relevance
“…In the study of Kunert et al, 2 % of meningiomas were associated with previous radiation treatment (c) Contrast-enhanced imaging confirms the classical appearance of meningiomas; the frontal lesion was histologically confirmed (Kunert et al 2012). The average time after initial treatment was 24 years, and some of the patients developed multiple tumors which was described as a common feature by Mansouri et al (2014) and is also found in our presented case. Long-term effects after radiation include the volume loss of brain parenchyma, often correlated with cognitive decline and diffuse white matter changes (Green-Schloesser and Robbins 2012; Rane and Quaghebeur 2012;Szerlip et al 2011;Lv et al 2014), the latter often seen after whole-brain irradiation.…”
Section: Imaging Findings After Radiation Of the Brainsupporting
confidence: 79%
See 1 more Smart Citation
“…In the study of Kunert et al, 2 % of meningiomas were associated with previous radiation treatment (c) Contrast-enhanced imaging confirms the classical appearance of meningiomas; the frontal lesion was histologically confirmed (Kunert et al 2012). The average time after initial treatment was 24 years, and some of the patients developed multiple tumors which was described as a common feature by Mansouri et al (2014) and is also found in our presented case. Long-term effects after radiation include the volume loss of brain parenchyma, often correlated with cognitive decline and diffuse white matter changes (Green-Schloesser and Robbins 2012; Rane and Quaghebeur 2012;Szerlip et al 2011;Lv et al 2014), the latter often seen after whole-brain irradiation.…”
Section: Imaging Findings After Radiation Of the Brainsupporting
confidence: 79%
“…Although rare, the most common induced tumors are meningiomas (Fig. 4) (Kunert et al 2012;Mansouri et al 2014;Madden et al 2010). In the study of Kunert et al, 2 % of meningiomas were associated with previous radiation treatment (c) Contrast-enhanced imaging confirms the classical appearance of meningiomas; the frontal lesion was histologically confirmed (Kunert et al 2012).…”
Section: Imaging Findings After Radiation Of the Brainmentioning
confidence: 99%
“…Previous ionizing radiation is a known cause of ONSM 4, 5. Such secondary meningiomas tend to present at a younger age, present with multiple lesions commonly arising from the sphenoid ridge, tuberculum sellae or olfactory groove and demonstrate a higher recurrence rate 4, 6, 7.…”
Section: Discussionmentioning
confidence: 99%
“…Previous ionizing radiation is a known cause of ONSM 4, 5. Such secondary meningiomas tend to present at a younger age, present with multiple lesions commonly arising from the sphenoid ridge, tuberculum sellae or olfactory groove and demonstrate a higher recurrence rate 4, 6, 7. Histopathology also suggests that they tend to be more aggressive, with a higher tendency toward malignancy in patients who had high nose radiation therapy 4, 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation